Epoxy-UHMWPE acetabular cup performance based on finite element study / Solehuddin Shuib ... [et al.] - Shuib, Solehuddin; Abd Manap, Muhammad Faris; Abdullah, Abdul Halim; Dimon, Mohd Zamrin; Romli, Ahmad Zafir; Ahmed Shokri, Amran (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
The articulate surface of the acetabular components are among the reasons of Total Hip Replacement (THR) failure. The types of the material used for the components are also equally important as the orientation of the acetabular component which must be complied to avoid failure. This study aims to find the mechanical properties of Epoxy-UHMWPE variants and compared with acetabular cup default material by using FEA. Two steps of methodology conducted; first by using hand technique layup for preparing Epoxy-UHMWPE samples and run compression testing, the second step is by re-run the data collected from the compression testing results into the FEA and compared with default material of acetabular cup. The results show that EpUHMWPE5 exhibits the highest Young's Modulus compared to other variants. The FEA run in ANSYS WORKBENCH V15 displayed that EpUHMWPE5 performs better compared to default material in term of Contact Pressure, Von-Mises stress and Total Deformation at 36mm femoral head with Maximum Safe Inclination Angle. The data of Contact Pressure, Von-Mises stress and Total Deformation for EpUHMWPE5 was at 5.0388MPa, 4.5042MPa and 0.01834mm compared to default material (UHMWPE) at 5.15MPa, 6.4211MPa and 0.02306mm, respectively. The results shows that EpUHMWPE5 could be a propose material to replace the UHMWPE material at the acetabular cup based on mechanical analysis aspect although further studies of the materials are compulsory.